Training of upgrading on a special platform and its impact on the special force and some starting variables and the completion of the long jump for young women - Saddam, Intisar Mezher (International Journal of Psychosocial Rehabilitation, 2020)
The success in the performance of horizontal jumping depends on mastering an appropriate and suitable approaching run to achieve the highest possible speed. Achieve a good flight path with a suitable starting angle and maintain body balance and fast shooting. This is related to the development of explosive force and this study came in the development of the advancement of the long jump of young women, through the adoption of a proposed upgrading platform that can be applied up lift and pushed the researcher used the experimental method in the manner of (equal groups) and applied research sample was selected from and prove the jump center of talent and the researcher prepared special exercises on the proposed platform jumping on the experimental group was carried out for 8 weeks and by two units weekly so the number of training units (16) training units, and was gradually loaded training by 1:3 in order to be training effective and active based on scientific foundations. The severity was determined according to the cut time and the physical effort was done separately. The researcher concluded that the exercises in the proposed platform influenced the improvement of the values of approach speed and the speed of starting at the moment of upgrading, as well as contributed to the change of the model of movement in the stage of increasing the height of the center of gravity of the body and the angle of starting at the moment of upgrading